CSR in education on business confidence: mediation effect of corporate reputation in the Peruvian banking sector - Lizarzaburu Bolaños, Edmundo R. (2022)
This paper analyzes the direct influence of CSR educational actions on business confidence in the context of the banking sector in an emerging country (Peru). A mediating effect through corporate reputation is also analyzed. To test the hypotheses presented in this paper, we have sent a survey to 1745 executive officers of the branches of the banks. These key individuals were selected as the target population of the study because the authors sought to study the management’s perception of CSR and business confidence. From the data obtained from the survey, it has been tested that educational CSR actions in Peruvian banks directly influences the perception of business confidence. Secondly, this relationship is partially mediated by the effect of CSR educational actions on corporate reputation.